2020
DOI: 10.1093/infdis/jiaa301
|View full text |Cite
|
Sign up to set email alerts
|

The Issue of Recurrently Positive Patients Who Recovered From COVID-19 According to the Current Discharge Criteria: Investigation of Patients from Multiple Medical Institutions in Wuhan, China

Abstract: The current discharge criteria for COVID-19 require that patients have two consecutive negative results for RT-PCR detection. Here, we observed that recurrently positive RT-PCR test results in patients with three consecutive negative results (3xNegRPos, 5.4%) were significantly decreased compared with those in patients with two consecutive negative results (2xNegRPos, 20.6%); such patients reported positive RT-PCR test results within 1 to 12 days after meeting the discharge criteria. These results confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 11 publications
1
55
2
Order By: Relevance
“…Reviewing cohort studies, case series, and case reports led to finding a total number of 1128 patients with the recurrence of SARS-CoV-2; 957 in cohort studies [ 1 , 13–28 ], 142 in case series [ 3 , 17 , 29–45 ] and 29 in case report studies [ 46–74 ]. The recurrence rate, which has been defined as positive SARS-CoV-2 RNA detection by RT-PCR test in patients who were recovered (showed negative RT-PCR test), was reported between 2.3% and 21.4% in cohort studies [ 1 , 13–19 , 21–28 , 75 ]. As an exception, a cohort study on paediatrics reported that seven patients out of 14 (50%) experienced recurrence [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reviewing cohort studies, case series, and case reports led to finding a total number of 1128 patients with the recurrence of SARS-CoV-2; 957 in cohort studies [ 1 , 13–28 ], 142 in case series [ 3 , 17 , 29–45 ] and 29 in case report studies [ 46–74 ]. The recurrence rate, which has been defined as positive SARS-CoV-2 RNA detection by RT-PCR test in patients who were recovered (showed negative RT-PCR test), was reported between 2.3% and 21.4% in cohort studies [ 1 , 13–19 , 21–28 , 75 ]. As an exception, a cohort study on paediatrics reported that seven patients out of 14 (50%) experienced recurrence [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…As an exception, a cohort study on paediatrics reported that seven patients out of 14 (50%) experienced recurrence [ 20 ]. Regardless of study type, based on 57 studies with available data (1019 patients), the first detection of recurrence of SARS-CoV-2 had been reported within a mean of 20 days, with a range of 1–140 days after meeting criteria for discharge [ 3 , 13 , 15–17 , 19–23 , 26–33 , 35–39 , 41–74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, patients with COVID-19 recover from infection within two weeks, particularly those with mild cases 2,3 . However, several reports have shown the prolonged presence of viral nucleotides (nts) in the upper or lower respiratory tract, lung tissues, or intestinal tract (fecal matter) in recovered patients [4][5][6][7] . Likewise, an estimated range of 10-20% recurrent positivity for viral nt was also reported 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, several reports have shown the prolonged presence of viral nucleotides (nts) in the upper or lower respiratory tract, lung tissues, or intestinal tract (fecal matter) in recovered patients [4][5][6][7] . Likewise, an estimated range of 10-20% recurrent positivity for viral nt was also reported 7 . SARS-CoV-2 RNA was still detected in nasopharyngeal swabs approximately 51 days after the onset of symptoms in a clinically recovered patient 5 .…”
Section: Introductionmentioning
confidence: 99%